CLINICOPATHOLOGIC FEATURES OF THYROID CANCER IN SULAIMANI, 2004-2018 - Nidhamalddin, Sara Jamil; Salai, Jangi Shawkat; Mohammed, Hazha Abdullah (Journal of Sulaimani Medical College, 2019)
Background Thyroid Cancer (TC) is the most common type of endocrine malignancy. Objectives To evaluate some of clinicopathologic features of thyroid carcinoma according to histopathology subtype, tumor size, age, sex and stage. Patients and Methods We conducted a retrospective study that included the patients with histologically proven thyroid cancer at Hiwa hematology /oncology cancer hospital of Sulaymaniyah from 2000 to June 2018. Retrospective evaluation of 225 cases of thyroid cancer during the study period carried out. Incidence of thyroid cancer with variations based on tumor histopathology, size(≤1 cm, 1.1-2 cm, 2.1-5 cm, ≥5 cm), and stage (local, regional, metastatic), age, and sex were analyzed among the different time periods of 2004-2008, 2009-2013 and 2014-2018. Results Thyroid cancer constituted (1.2%) of total solid cancers registered. A total number of 195 cases, 80 %( 155) female 20 %( 40) male of Thyroid Cancer (TC) identified from 2004-2018, only 8(4.1%) of the cases diagnosed in 2004-2008, while (142) 72.8% of the cases diagnosed in 2014-2018. Female/male ratio was 3.87. Mean age was 41.52 years, 67% of them were below age 45. Proportion of patients with tumor localized to thyroid gland (local stage) was 63%. The mean size of tumors at diagnosis was 21.71 mm at their longest diameter. Most common histologic feature was papillary thyroid cancer constituting 82% of all cases of thyroid cancer Conclusion Papillary thyroid cancer (PTC) was the most common type of registered thyroid cancer. Thyroid cancer was more common among females. The current study showed that the disease tends to occur at a younger age, small size and more localized to thyroid gland.
Keywords: Thyroid cancer; incidence; Overdiagnosis; Clinicopathologic feature